Literasi Lingkungan Perubahan Iklim dan Dampaknya terhadap Ekosistem Laut dan Masyarakat Pesisir - Haumahu, Sara; Pasanea, Krisye; Supusepa, Junita; Fakaubun, Fahrul Rozi (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
Climate change is a global threat whose impacts are felt in various sectors including marine ecosystems and coastal communities. Increasing sea surface temperatures, rising sea levels are some of the significant impacts of climate change. The socialization of environmental literacy about climate change and its impacts on marine ecosystems and coastal communities for students of Senior High School (SMA) 9 Ambon aims to provide a comprehensive understanding of climate change issues, and to increase student knowledge and skills to adapt and reduce the negative impacts of climate change. This community service (PKM) activity was carried out by lecturer staf of Marine Science Department of Faculty of Fisheries and Marine Science, Pattimura University, Ambon on February 14, 2025, attended by 60 participants and 4 members of the Socialization Team. The socialization method used was lectures. Evaluation was carried out through questionnaires and discussions during the activity. As many as 85% of students had a very good level of understanding of the material provided. Student enthusiasm was very high in participating in this socialization activity. It is hoped that this activity can be carried out continuously for students in various high schools on Ambon Island.